2019
DOI: 10.1159/000495504
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radioiodine Treatment on TRAb, Anti-TPO, and Anti-TG in Graves’ Disease

Abstract: Background: In Graves’ disease (GD), immunocompetent cells infiltrate thyroid tissue with release of TSH-receptor antibodies (TRAb), and radioiodine treatment is known to elicit an immune response with an increase in TRAb. Objectives: The aim was to study if all patients treated with radioiodine respond with a release of TRAb, anti-thyroperoxidase (anti-TPO), and anti-thyroglobulin (anti-TG). Methods: This is a prospective observational study. GD patients (n = 131) were admitted for treatment with radioiodine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
5
14
0
Order By: Relevance
“…These findings were confirmed by other studies (24), and these peaks were correlated with the development of GO (12,26). TRAb remaining positive after years may 2…”
Section: Serum Trab During Atd Therapysupporting
confidence: 84%
See 1 more Smart Citation
“…These findings were confirmed by other studies (24), and these peaks were correlated with the development of GO (12,26). TRAb remaining positive after years may 2…”
Section: Serum Trab During Atd Therapysupporting
confidence: 84%
“…The use of ATD is accompanied by a series of markers demonstrating immune system restoration, such as decreased HLA in thyroid cells (17), and decreased markers of inflammation, such as Interleucines 1, 5, and 6 and tumor necrosis factor-alpha (18,19). There are also increases in T cell suppressors, decreases in T helper cells (20), and decreases in TRAb values over time (9,10,(21)(22)(23)(24).…”
Section: Serum Trab During Atd Therapymentioning
confidence: 99%
“…We have shown that 3 months after treatment with radioiodine, two groups of patients were identi ed according to antibody response, one group that did not increase in TRAb, anti-TPO and anti-TG (approximately 30 % of the patients) and one group that increased in antibodies (approximately 70% of the patients). This has previously been demonstrated in a smaller group of GD patients [15]. The second observation was that the risk of developing GO was clearly elevated in patients which increased in TRAb 3 months after radioiodine.…”
Section: Discussionsupporting
confidence: 61%
“…In vitro it has been shown that a mixture of immunocompetent cells in Hashimoto produces thyroid speci c antibodies after irradiation, and this effect was dose dependent [11]. We have previously studied the effect of the dose of radioiodine, but we could not con rm this in vivo [15]. Another hypothesis is that a transient increase in thyroid antigen like thyroglobulin will be released when cells are destroyed by irradiation [9,10].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation